Experimental Study on the Impact of Wet Sand Particle to the Erosion of Mild Steel Plate - AMIRUL LUTHFI CHAN, HAZIQ LUTHFI (IRC, 2016)
Flow-lines erosion due to the impact of sand particles or sanding is a problem of practical significance in almost all areas of the oil and gas and other closely related industries. This study investigated the wet erosion of mild steel plate by conducting a single phase flow wet sand impact erosion test. Three main parameters that the author needs to consider for this experiment are the fine particles, pipelines and fluid flow. An experimental rig to conduct a single phase flow wet sand impact erosion test will be setup and scanning electron microscopy (SEM),energy-dispersive X-ray spectroscopy (EDS) , surface roughness and Vickers micro- hardness techniques will be used to quantify the effect of fine particle on the erosion rate of the exposed surface.